expand and simplify: (5x^2 + 1)(2x+3)-2x(5x^2 - 3). Show your working

1 answer

(5x^2 + 1)(2x+3)-2x(5x^2 - 3)

= 10x^3 +15x^2 +2x +3 -10x^3 +6x

= 15x^2 +8x +3

Working:

(5x^2 + 1)(2x+3)

= (5x^2)(2x) + (5x^2)(3) + (1)(2x) + (1)(3)

= 10x^3 +15x^2 +2x +3

-2x(5x^2 - 3)

= -2x(5x^2) +2x(3)

= -10x^3 +6x

Thus, combining the like terms, we get

(5x^2 + 1)(2x+3)-2x(5x^2 - 3) = 15x^2 +8x +3
Similar Questions
    1. answers icon 1 answer
  1. Show that:(3x-1)(x+5)(4x-3) = 12x^3 + 47x^2 - 62x +15 for all values of x. (3x-1)(x+5)(4x-3) = (?????)(4x-3) Expand into 6
    1. answers icon 3 answers
    1. answers icon 1 answer
    1. answers icon 1 answer
more similar questions